A-SURE: intra-patient comparison of prophylactic effectiveness of a recombinant factor VIII Fc fusion protein versus standard half-life factor VIII in hemophilia A - Johannes Oldenburg; Charles Hay; Flora Peyvandi; Anna-Elina Lehtinen; Ingrid Pabinger; Eveline Nüesch; Håkan Malmström; Eva Bednar; Stefan Lethagen (Hematology, 2025)
Background Despite recent advances, factor replacement therapy remains a cornerstone in hemophilia A treatment. Efmoroctocog alfa, a recombinant FVIII Fc fusion protein (rFVIIIFc), has an extended half-life allowing higher FVIII levels and less frequent dosing than standard half-life (SHL) products, without increasing factor consumption.Methods A-SURE was a 24-month prospective, non-interventional study assessing real-world effectiveness of rFVIIIFc prophylaxis. This post-hoc, intra-patient analysis included patients with hemophilia A (PwHA) who switched from SHL FVIII to rFVIIIFc prophylaxis. Effectiveness endpoints included annualised bleeding rate (ABR), annualised joint bleeding rate (AjBR), weekly injection frequency and weekly factor consumption.Results Of 131 PwHA eligible for analysis, mean ABR and AjBR decreased from 3.7 and 2.4 to 1.8 and 1.1, respectively, after switching (mean [95% confidence interval (CI)] change of −1.9 [−3.0, −0.8] and −1.2 [−2.0, −0.5]). Mean weekly injection frequency decreased from 3.1 to 2.3 (mean [95% CI] change of −0.8 [−1.0, −0.7]); weekly factor consumption reduced from 89.7 to 84.1 international units (IU)/kg, respectively (mean [95% CI] change of −5.7 [−10.7, −0.6]). These trends were consistent across age groups.Conclusion This intra-patient comparison demonstrates switching from SHL FVIII to rFVIIIFc prophylaxis reduces frequency of bleeds, injection frequency, and factor consumption, complementing previously reported data from A-SURE.Trial registration:ClinicalTrials.gov identifier: NCT02976753.